A SYSTEMATIC LITERATURE REVIEW ON ROLE OF PROJECT MANAGEMENT IN DIGITAL FORENSICS INVESTIGATION - Panji Zulfikar Sidik; Teguh Raharjo (LPPM Nusa Mandiri, 2024)
The landscape of digital forensics has evolved significantly with the advent of sophisticated cybercrimes and the proliferation of digital devices. Digital forensics is a rapidly evolving discipline, characterized by unique challenges such as rapidly changing technology, large volumes of data, and stringent legal requirements. Effective project management in this context is crucial to ensure that investigations are conducted efficiently, accurately, and in compliance with legal standards. This systematic literature review aims to comprehensively analyze the role of project management practices in optimizing digital forensics investigations. Using established search protocols and selection criteria, we identified and analyzed relevant studies published between 2016 until 2023 that explored the application of project management methodologies, challenges, and best practices within the context of digital investigations. By applying effective project management strategies, investigators can ensure efficient, accurate, and legally sound digital investigations, ultimately contributing to successful criminal prosecutions and civil litigation outcomes.